Rationale and Design of the International Lymphoma Epidemiology Consortium (InterLymph) Non-Hodgkin Lymphoma Subtypes Project. Issue 48 (30th August 2014) - Morton, Lindsay M.; Sampson, Joshua N.; Cerhan, James R.; Turner, Jennifer J.; Vajdic, Claire M.; Wang, Sophia S.; Smedby, Karin E.; de Sanjosé, Silvia; Monnereau, Alain; Benavente, Yolanda; Bracci, Paige M.; Chiu, Brian C. H.; et al.
Abstract: Background: Non-Hodgkin lymphoma (NHL), the most common hematologic malignancy, consists of numerous subtypes. The etiology of NHL is incompletely understood, and increasing evidence suggests that risk factors may vary by NHL subtype. However, small numbers of cases have made investigation of subtype-specific risks challenging. The International Lymphoma Epidemiology Consortium therefore undertook the NHL Subtypes Project, an international collaborative effort to investigate the etiologies of NHL subtypes. This article describes in detail the project rationale and design. Methods: We pooled individual-level data from 20 case-control studies (17471 NHL cases, 23096 controls) from North America, Europe, and Australia. Centralized data harmonization and analysis ensured standardized definitions and approaches, with rigorous quality control. Results: The pooled study population included 11 specified NHL subtypes with more than 100 cases: diffuse large B-cell lymphoma ( N = 4667), follicular lymphoma ( N = 3530), chronic lymphocytic leukemia/small lymphocytic lymphoma ( N = 2440), marginal zone lymphoma ( N = 1052), peripheral T-cell lymphoma ( N = 584), mantle cell lymphoma ( N = 557), lymphoplasmacytic lymphoma/Waldenström macroglobulinemia ( N = 374), mycosis fungoides/Sézary syndrome ( N = 324), Burkitt/Burkitt-like lymphoma/leukemia ( N = 295), hairy cell leukemia ( N = 154), and acute lymphoblastic leukemia/lymphoma ( N = 152). Associations with medical history, family history, lifestyle factors, and occupation for each of these 11 subtypes are presented in separate articles in this issue, with a final article quantitatively comparing risk factor patterns among subtypes. Conclusions: The International Lymphoma Epidemiology Consortium NHL Subtypes Project provides the largest and most comprehensive investigation of potential risk factors for a broad range of common and rare NHL subtypes to date. The analyses contribute to our understanding of the multifactorial nature of NHL subtype etiologies, motivate hypothesis-driven prospective investigations, provide clues for prevention, and exemplify the benefits of international consortial collaboration in cancer epidemiology.